Serum lipid profile in patients with ischaemic stroke the - correlation between them - Dr Sanjay Goyal, Dr Sanjay Kumar Goyal; Dr Sachin Kaushal; Dr Amritpal Singh; Dr Dawantremi Challam; Dr Deeplekh Singh; Dr Manjot Singh Bhaura (GMC Patiala Journal of Research and Medical Education, 2022)
Objective: The purpose of the study was to study the serum lipid profile in patients with ischaemic stroke and to determine significant correlation between them. Materials and Methods: Study design : Cross sectional study of one year. Study Centre : Patients admitted in the indoor wards of Medicine Department of Govt Medical College and Rajindra Hospital , Patiala. Method of Collection of Data : A minimum of 50 patients aged >35yrs, both male and females who were diagnosed to have ischaemic cerebrovascular disease and who matched the inclusion and exclusion criteria were selected. Results: Mean age in this study was 59.48 years. Among the study population, 24 (48%) were males and 26 (52%) were females. Most of ischaemic stroke patients (90%) fell in the 40-79 years age group and Dyslipidemia was observed in 78 % of ischaemic stroke patients enrolled in this study . Highest prevalence of ischaemic stroke is found in the 60-69 years age group. Among ischaemic stroke patients with dyslipidemia enrolled in this study the frequency of lipid profile derangements were as follows : -Deranged HDL (males <35.3mg/dL, female <42mg/dL) in 61.5 % of Ischemic stroke patients -Deranged total cholesterol (>200 mg/dl) in 46.2 % of ischaemic stroke patients. - Deranged Triglycerides in (>161mg/dL) in 25.6 % of ischaemic stroke patients. -Deranged LDL in (>153mg/dL) in 23.1 % of ischaemic stroke patients. -Deranged VLVL (>40mg/dL) in 7.7 % of ischaemic stroke patients. Conclusion: Hence ,we could conclude from our study that dyslipidemia is associated with ischemic stroke. This also underlines the importance of identifying the risk factors of ischaemic stroke as early identification and modification of risk factors may help reduce the occurrence of stroke. However, more data and studies are required especially in Indian context to accurately define the relationship of dyslipidemia with ischmic stroke.